Urban Transport Policies: The Dutch Struggle with Market Failures and Policy Failures - Piet Rietveld (Tinbergen Institute, 2004)
Transport is characterised by market failures that are of particular importance in urban settings. This paper reviews market failures and policy failures in The Netherlands for various transport markets, including road transport, public transport and biking. Special attention is paid to parking problems, and possibilities to cope with these by pricing measures. It is demonstrated that in some cases parking externalities lead to non-convexities that make pricing policies less attractive. In that case parking restrictions are called for. A general shift is observed from national to municipality policy initiatives. In terms of both effectiveness and social and political acceptability, the municipal policies definitely score better.
Keywords: R41; R42; R48; 330; parking; infrastructure; pricing; bicycle use; market failure; Stadtverkehrspolitik; Ruhender Verkehr; Öffentlicher Nahverkehr; Marktversagen; Staatsversagen; Niederlande